(untitled) (Praxis Educativa, 2013)
Doing research implies an intention to deepen our knowledge of the world we are immersed in and a better understanding of our reality, which also worries us, and is able to set the basis for a more adequate intervention as to the circumstances and aspirations which guide us. But the way to knowledge is not free from obstacles, many of which appear to our conscience, at first sight, as an aid. This research paper intends, from a non-canonical point of view, to show some of the difficulties we have to confront when we start doing research work. To consider the task of doing research is an unavoidable commitment for all those researchers who have the responsibility of training professionals in education that contribute to foster a genuine inclusion of their students, based on a critical acquisition of socially validated knowledge.